PENGARUH REBUSAN CACING AFRICAN NIGHT CRAWLER TERHADAP PERTUMBUHAN BAKTERI SALMONELLA THYPI - Aini (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2022)
Previous studies have conducted experiments using earthworms. The results showed that earthworms were able to inhibit the growth of Salmonella typhi bacteria. The purpose of this study was to determine the effect of different concentrations of boiled water for African night crawler earthworms on the resulting inhibition zone. The type of research used is experimental research. The population of this study was the African night crawler worm in Narmada District. The sample of this study was the African night crawler worm in Batu Kantar Hamlet, Narmada Village, Narmada District.The conclusion of this study was that there was no effect of different concentrations of boiled water for African night crawler earthworms on the inhibition zone including the medium inhibition zone formed in the first treatment until the fifth treatment was different, this happened because of the difference in thickness and thickness of the pure strain of Salmonella typhosa on the media. Muller Hinton Agar (MHA).